Suicidal Behavior and Neurological Illnesses - Coughlin, Steven S (2013)
OBJECTIVE: Suicidal ideation and behavior have been associated with a variety of neurological illnesses. Studies are ongoing in combat veterans and other groups to examine possible mechanisms and pathways that account for such associations. METHOD: This article provides a review of the literature on suicide ideation and suicidal behavior in patients with neurological illnesses including publications on veteran’s health and military medicine. Studies of suicide attempts and deaths in people with neurological illnesses are also reviewed. RESULTS: The studies summarized in this review indicate that there are important linkages between suicidal ideation and behavior and neurological conditions, including epilepsy, multiple sclerosis, and amyotrophic lateral sclerosis. CONCLUSION: Additional studies are needed to further clarify why suicide ideation and suicidal behavior are associated with neurological diseases, in order to improve quality of life, alleviate patient distress, and prevent nonfatal and fatal suicide attempts in veteran and non-veteran populations.